Alta hospitalar responsável: dispositivo para a continuidade do cuidado de pessoas com diabetes mellitus - Natalia, Ferrari Vedroni (2024)
The organization of the Health Care Network (HCN) is an inherent component of the Unified Health System (SUS) that ensures comprehensive care, playing a role in a context where primary health care takes on a central role as the care coordinator. Based on this concept, the present research aims to analyze the contribution of responsible hospital discharge in the continuity of care for individuals with Diabetes Mellitus, a chronic disease that affects a significant portion of the population and has important social, economic, and family repercussions. The increasing prevalence of Diabetes Mellitus leads to complications that directly impact the quality of life and functional capacity of patients. Therefore, it becomes essential to verify strategies that ensure continuity of care after hospital discharge. In this sense, responsible hospital discharge is understood as a practice that can facilitate the transition of care, minimizing the possibility of readmissions, and also promoting better adherence and continuity of treatment. The methodological approach used was qualitative, through the application of a semi-structured questionnaire to individuals hospitalized with Diabetes Mellitus. This methodology allowed for an in-depth assessment of the participants' health needs and the effectiveness of care processes related to hospital discharge. The results obtained highlighted weaknesses in comprehensive health care, pointing to the scarce connection between users and health services. The evidence suggests that the lack of a strong bond and active listening results in challenges in the continuity of care, reinforcing the need for investments in primary care. Furthermore, the research points to the urgency of developing effective strategies for the organization of the HCN, promoting continuous qualification of health professionals, and implementing reviews of work processes. Permanent education also stands out as an essential factor for improving care practices, enabling professionals to meet the health demands of the population. These findings not only contribute to the discussion on the importance of comprehensive care but also offer insights for the formulation of public policies aimed at improving health services, especially regarding the care of chronic non-communicable diseases. Keywords: Health Care Network; Responsible Hospital Discharge; Comprehensive Care; Chronic Non-Communicable Diseases.